High Content Imaging and Quantification of Microglia Phagocytosis In Vitro. Issue 1 (9th January 2023) - McPherson, Christopher A.; Kelly‐Rajan, Kiran; Lefebvre d'Hellencourt, Christian; Harry, G. Jean
Abstract: Microglia function as the tissue‐specific resident macrophages of the nervous system, performing immune and non‐immune functions. These functions are critical to development and to maintain homeostasis in the nervous system throughout the lifespan, and during brain injury or disease. One method by which microglia maintain homeostasis is phagocytosis of aberrant proteins, extracellular debris, synapses, or apoptotic cells. Phagocytic function can be changed by environmental or genetic risk factors that affect microglia. These protocols present a rapid and simple in vitro high‐content imaging protocol for studying phagocytosis in the murine microglia BV‐2 cell line. High‐content imaging and analysis enable versatility of the assay, which can be used to test multiple experimental conditions, or as a screening tool. © 2023 Wiley Periodicals LLC. This article has been contributed to by U.S. Government employees and their work is in the public domain in the USA. Basic Protocol 1 : Phagocytosis of fluorescently labeled particles Basic Protocol 2 : Examining modifications to phagocytosis by test substances Basic Protocol 3 : High content imaging and analysis of phagocytic cells